STUDI FOTOGRAMETRI RENTANG DEKAT MENGGUNAKAN DRONE MULTIROTOR RTK UNTUK PENGUKURAN BIDANG TANAH - Calvin Brena Ginting, Michael
Acceleration of land measurement and mapping is intensively carried out due to the increasing of society demands, furthermore accompanied by government programs to provide land certificates for its people through the PTSL program. Conventional mapping methods are considered less able to fulfill the idea. The close range photogrammetry method is an alternative method for land mapping. This study examines the ability of close range photogrammetry techniques through unmanned aerial vehicles (UAV) to carry out measurements and mapping of plots of land in order to speed up the process of land registration in accordance with the orderly land administration program. This study was carried out by measuring several samples of land using unmanned vehicles that have the ability to determine the position in real time kinematic (RTK). The coordinates, distance and area values obtained from the digital photogrammetry processing are checked for their accuracy with respect to direct measurements using the GNSS RTK by the value of Root Mean Square Error (RMSE). The accuracy is compared with the geometry accuracy standards set by the National Land Agency (BPN) and the Geospatial Information Agency (BIG) to obtain conclusions from the evaluations conducted. The results showed the accuracy of the coordinates, distance and area had met the specified requirements.